Beyond the big city: using a systems approach to cultivate a cycling culture in small cities and towns in Ireland - Corr, Caitriona; Murphy, Niamh; Lambe, Barry (Frontiers in Sports and Active Living, 2023)
Urban mobility and how people move in our towns and cities is garnering more attention, as solutions are sought to multiple challenges faced by residents; health and physical inactivity, climate change, air quality, urbanisation and accessibility. Traditional, siloed approaches limit impact and collaborative, systems approaches hold promise. However, systems approaches often remain theoretical and few practical applications of their added value have been demonstrated. This study illustrates how a systems approach can be used to underpin the development of a 9-step process to generate solutions for action on active mobility. The development of a systems map and a theory of change framework are key outputs of this 9-step process. The purpose of this paper is to describe how a systems map was developed in an Irish town utilising broad stakeholder engagement to map the variables that influence cycling in the town and to identify the leverage points for transformational interventions.